2019
DOI: 10.1161/circresaha.118.313926
|View full text |Cite
|
Sign up to set email alerts
|

Heterocellular Contact Can Dictate Arterial Function

Abstract: Rationale: Resistance arteries and conduit arteries rely upon different relative contributions of endothelial derived hyperpolarization (EDH) versus nitric oxide (NO) to achieve dilatory heterocellular signaling. Anatomically, resistance arteries use myoendothelial junctions (MEJs), endothelial cell (EC) projections that make contact with smooth muscle cells (SMCs). Conduit arteries have very few to no MEJs. Objective: Determine if the presence of MEJs in conduit arteries can alter heterocellular signaling. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 44 publications
1
45
0
Order By: Relevance
“…S7). These data are consistent with a recent study demonstrating that delivery of recombinant PAI-1 to carotid arteries induces myoendothelial junction formation, reduces NO signaling, and enhances endothelial-derived hyperpolarization signaling (45). Moreover, recent studies suggest that PAI-1 is not only a critical marker and mediator of senescence (46,47), but that it is intimately linked to aging (48), and individuals with a null mutation in PAI-1 have a longer lifespan (49).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…S7). These data are consistent with a recent study demonstrating that delivery of recombinant PAI-1 to carotid arteries induces myoendothelial junction formation, reduces NO signaling, and enhances endothelial-derived hyperpolarization signaling (45). Moreover, recent studies suggest that PAI-1 is not only a critical marker and mediator of senescence (46,47), but that it is intimately linked to aging (48), and individuals with a null mutation in PAI-1 have a longer lifespan (49).…”
Section: Discussionsupporting
confidence: 91%
“…Pressure Myography of Cannulated Arteries. As described previously (45,66), third order mesenteric arteries were removed, cannulated, and pressurized to 60 mmHg. Arteries were washed with a Ca 2+ -free Krebs-Hepes solution to obtain maximal passive diameter of the vessels.…”
Section: Methodsmentioning
confidence: 99%
“…6A), suggesting that regulation of eNOS activity, rather than its expression, underlies the differential contribution of eNOS in PAs and MAs. Because Hbα has been shown to interact with eNOS and scavenge NO, thereby limiting NO bioavailability (Straub et al 2012;Keller et al 2016;Shu et al 2019), we hypothesized that Hbα limits the role of eNOS-NO signalling in MAs. Immunostaining studies showed minimal expression of Hbα in ECs from PAs but confirmed strong expression and localization of Hbα at MEPs in MAs (Fig.…”
Section: Hbα Localizes With Enos At Meps In Mas But Not In Pasmentioning
confidence: 99%
“…HbαX, a peptide that inhibits the interaction of Hbα with eNOS, (Straub et al 2014;Keller et al 2016;Shu et al 2019), was used to determine whether Hbα-eNOS interactions limit the role of eNOS in MAs; Scr X was used as a control. Both HbαX and Scr X possess a tat tag, which has previously been shown to render these peptides cell permeable (Straub et al 2014;Keller et al 2016;Shu et al 2019). Strikingly, MAs treated with HbαX were capable of constricting in response to L-NNA, suggesting that Hbα and eNOS normally interact in these arteries and that disruption of Hbα-eNOS interactions with HbαX disinhibited TRPV4 EC -eNOS signalling.…”
Section: Hbα Localizes With Enos At Meps In Mas But Not In Pasmentioning
confidence: 99%
“…Endothelial stimulation with agonists or by shear stress increases the intracellular calcium concentrations, which in turn generates endothelial hyperpolarization through the opening of small (SK Ca ) and intermediate conductance (IK Ca ) Ca 2+ -activated K + channels [2,3,4,5,7]. Then, in a number of arteries in which MEGJs exist, the endothelium-dependent hyperpolarization (EDH) spreads to adjacent smooth muscle cells via MEGJs, leading to vasorelaxation [2,3,4,5,8,9]. Although the intracellular Ca 2+ release from the endoplasmic reticulum (ER) and the subsequent activation of the SK Ca and IK Ca channels is an initial step for the generation of EDH [3,4,7], the Ca 2+ influx through endothelial nonselective cation channels of the transient receptor potential (TRP) family after ER calcium depletion also contributes to the generation of EDH via the downstream activation of SK Ca and IK Ca channels (Figure 1) [2,3,4,5,10,11,12].…”
Section: Introductionmentioning
confidence: 99%